The synthesis and characterisation of curcumin loaded Ag (1-X) Ni X Fe2 O4 for drug delivery. (12th May 2021) - Jose, Riya; J, Rinita.; Jothi, N.S.Nirmala
ABSTRACT: A simple procedure of solvothermal synthesis of Silver doped Nickel ferrite nanoparticle is described in this paper for the application of drug delivery. The microwave absorption and SERS phenomena of silver nanoparticles and water-absorbent property of the polymer material such as polyethylene glycol (PEG) to bypass fast identification by the antibodies are made use in the synthesis of Ag-doped nickel ferrite with PEG as a solvent. The ferrite sample was distinguished using XRD, FTIR, SEM, TEM, and VSM. The absorption wavelength and corresponding band gap energy were calculated by UV-Vis spectroscopy. The drug delivery efficiency of silver doped nickel ferrite sample was conducted with curcumin by changing pH, initial drug concentration and specified magnetic field. Results prove that the addition of silver and polyethylene glycol in nickel ferrites changes the properties of the nanoparticle and recognised as a good material for drug delivery applications.